The Documentary Art of Filmmaker Michael Rubbo - Art Jones, Documentary D.B (Cinemas Off Centre, 2017)
Michael Rubbo's groundbreaking work has had a deep and enduring impact on documentary filmmaking worldwide, though his name has remained relatively unknown. In The Documentary Art of Michael Rubbo, author D.B. Jones traces Rubbo's filmmaking from his days as a film student at Stanford, through his twenty years at the National Film Board of Canada, where Rubbo developed his distinct documentary style. Jones then describes Rubbo's post-NFB venture into feature film directing, followed by Rubbo's return to his native Australia, first as an executive with the Australian Broadcasting Corporation, and later as a director of feature-length documentaries and maker of short, personal films for YouTube. Exploring locales from Montreal to Vietnam, topics as diverse as plastic surgery and French Marxism, and from interviewing Margaret Atwood to documenting a failed attempt to interview Fidel Castro, Rubbo's wide-ranging work establishes his innovative, personal, lyric, and spontaneous documentary style. In The Documentary Art of Michael Rubbo D.B. Jones reveals not only the depth of meaning in Rubbo's films, but also the depth of their influence on filmmaking itself.